Blood Glucose Levels, Platelet Count, and Urinary Ketone Levels in Lame Bali Cattle - Jayanti, Putu Devi; Gunawan, I Wayan Nico Fajar (Universitas Airlangga, 2024)
Lameness is a common problem in Bali cattle. It is caused by various factors, both infectious and non-infectious. This study aims to evaluate the physiological changes in the levels of blood glucose and urinary ketone in lame Bali cattle. This study included 18 Bali cattle with locomotive disorders. Blood glucose levels were assessed from blood samples taken from the jugular vein, while urinary ketone levels were assessed from manually taken urine samples during urination of Bali cattle. The results showed that Bali cattle with locomotive disorders had significantly low blood glucose levels as well as mild to moderate ketonuria and thrombocytosis, which were associated with the increased energy requirements of lame cattle for maintaining postural balance. The results also suggested that the incidence of lameness in Bali cattle was relatively high.